Adenomatous polyposis coli is differentially distributed in growth cones and modulates their steering - Köster, Michael; Müller, Oliver; Pollerberg, G. Elizabeth (The journal of neuroscience, 2007)
Axonal steering reactions depend on the transformation of environmental information into internal, directed structures, which is achieved by differential modulation of the growth cone cytoskeleton; key elements are the microtubules, which are regulated in their dynamics by microtubule-associated proteins (MAPs). We investigated a potential role of the MAP adenomatous polyposis coli (APC) for growing axons, employing embryonic visual system as a model system. APC is concentrated in the distalmost (i.e., growing) region of retinal ganglion cell axons in vivo and in vitro. Within the growth cone, APC is enriched in the central domain; it only partially colocalizes with microtubules. When axons are induced to turn toward a cell or away from a substrate border, APC is present in the protruding and absent from the collapsing growth cone regions, thus indicating the future growth direction of the axon. To assess the functional role of the differential distribution of APC in navigating growth cones, the protein was inactivated via micro-scale chromophore-assisted laser inactivation in one half of the growth cone. If the N-terminal APC region (crucial for its oligomerization) is locally inactivated, the treated growth cone side collapses and the axon turns away. In contrast, if the 20 aa repeats in the middle region of APC (which can negatively regulate its microtubule association) are inactivated, protrusions are formed and the growth cone turns toward. Our data thus demonstrate a crucial role of APC for axon steering attributable to its multifunctional domain structure and differential distribution in the growth cone.